The tobacco wives : a novel - Myers, Adele (Writer) (William Morrow, an imprint of HarperCollins Publishers, 2022)
In 1946 North Carolina, seamstress Maddie Sykes, a dressmaker for Bright Leaf's most influential women--the wives of powerful tobacco executives, uncovers dangerous truths about this lucrative industry in a place where everyone depends on Big Tobacco to survive.